A Mathematical Model for Vineyard Replacement with Nonlinear Binary Control Optimization - Galindro, Aníbal; Cerveira, Adelaide; Torres, Delfim F. M.; Matias, João; MartaCosta, Ana (Discontinuity, Nonlinearity, and Complexity, 2026)
Vineyard replacement is a common practice in every wine-growing farm since the grapevine production decays over time and requires a new vine to ensure the business sustainability. In this paper, we formulate a simple discrete model that captures the vineyard’s main dynamics such as production values and grape quality. Then, by applying binary non-linear programming methods to find the vineyard replacement trigger, we seek the optimal solution concerning different governmental subsidies to the target producer.